Measuring the Multidimensional Impact of University of Jaffna Research: An Altmetric-Based Evaluation - Janen, T. (Eastern University, Sri Lanka, 2025)
This study aims to measure the overall social media visibility, societal impact and analyze the policy influence in national and international policy documents of research publications of University of Jaffna (UoJ) using Altmetric data. Analysis of the Altmetric Attention Score (AAS) shows that, UoJ research publications received 2,512 total mentions among those 1,972 mentions from social media, 254 news and blogs, 182 mentions in policy, patents and guidelines etc. Seventy-five publications were mentioned in World Health Organization (WHO) policy sources. Open access publications received more AAS than closed access and among the open access, bronze open access received highest AAS and dimension citation. Trend of AAS shows fluctuating pattern and in general it increasing over the time. Among the different social media platforms, X-mentions is a dominant platform to publicize UoJ publications. Psychology (n=25.83) and biomedical clinical sciences (n= 22.03) received highest average AAS it indicates the strong social media interest than other research publications by UoJ. Research output related to psychology also perform well in dimension citation and it reflecting academic impact. There is a considerable mismatch in some research areas that are highly cited academically may not get proportionate attention in Altmetric and vice versa. The result significantly shows the usage of research outputs by the national and international level policy documents. It bought as a valuable indicator of real world influence especially these publications have been cited in global health policies published by WHO. This study highlights the multidimensional impact of UoJ research, demonstrating that Altmetrics complement traditional citations by capturing immediate societal and policy influence. The study recommends strengthening open access publishing and researcher engagement on social media while incorporating Altmetrics into institutional evaluations to enhance visibility and societal impact. Growth and supporting future academic planning and development.
Keywords: University of Jaffna; Altmetric attention score (AAS); Dimension citation; Social media impact; Societal impact